Binding of von Willebrand Factor to Collagen Type III: Role of Specific Amino Acids in the Collagen Binding Domain of vWF and Effects of Neighboring Domains - van der Plas, R. Martijn; Gomes, Lucio; Marquart, J. Arnoud; Vink, Tom; Meijers, Joost C. M.; de Groot, Philip G.; Sixma, Jan J.; Huizinga, Eric G. (Thrombosis and Haemostasis, 2000)
Binding of von Willebrand Factor (vWF) to sites of vascular injury is the first step of hemostasis. Collagen types I and III are important binding sites for vWF. We have previously determined the threedimensional structure of the collagen binding A3 domain of vWF (Huizinga et al., Structure 1997; 5: 1147). We hypothesized that the top face of this domain might be the collagen-binding site. Based on this hypothesis, we made seven vWF mutants (D934A/S936A, V1040A/ V1042A, D1046A, D1066A, D1069A, D1069R, and R1074A). Collagen binding of these mutants was investigated in ELISA and with Surface Plasmon Resonance (BIAcore). In addition, we studied collagen binding of mutants lacking the A2 or D4 domains, which flank the A3 domain.In ELISA, all point mutants and deletion mutants bound to collagen in amounts similar to wild type (WT)-vWF. In the BIAcore we found that WT-vWF has an apparent KD for collagen of 1-7 nM on a subunit base. The apparent kinetic parameters of the point mutants and deletion mutants were not significantly different from WT-vWF, except for DA2-vWF, which had a lower KD, indicating that the A2 domain somehow modulates binding of vWF to collagen type III.Based on our results, we conclude that the amino acid residues mutated by us are not critically involved in the interaction between vWF and collagen type III, which suggests that the collagen binding site is not located on the top face of the A3 domain.
Keywords: von Willebrand factor; collagen; mutagenesis; A-domains; platelet adhesion